2009
DOI: 10.1245/s10434-009-0797-6
|View full text |Cite
|
Sign up to set email alerts
|

Obesity and Angiolymphatic Invasion in Primary Breast Cancer

Abstract: Background Obesity is associated with poorer breast cancer-specific survival. The purpose of this study was to investigate the relationships between obesity and the presence of angiolymphatic invasion as well as other features of invasive breast cancer, including stage at presentation, estrogen receptor (ER) status, the triple-negative phenotype, and tumor grade. Methods Detailed clinical and pathologic data were abstracted from the medical records of all 1,312 patients with Stage I – III primary breast canc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
27
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(33 citation statements)
references
References 50 publications
6
27
0
Order By: Relevance
“…It was concluded that menopausal status may be a factor mitigating the effect of obesity on the incidence of TNBC. A South American study drew similar conclusions, but this may be attributed to the higher incidence rates of TNBC observed among younger women of African American descent (15 (17). From this research, the high rates of TNBC have been primarily attributed to diabetes.…”
Section: Tnbc Patients Tend To Have Larger Tumors Higher T Stage Andmentioning
confidence: 56%
“…It was concluded that menopausal status may be a factor mitigating the effect of obesity on the incidence of TNBC. A South American study drew similar conclusions, but this may be attributed to the higher incidence rates of TNBC observed among younger women of African American descent (15 (17). From this research, the high rates of TNBC have been primarily attributed to diabetes.…”
Section: Tnbc Patients Tend To Have Larger Tumors Higher T Stage Andmentioning
confidence: 56%
“…IL-6 has mitotic and anti-apoptotic effect and higher levels of IL-6 is associated with poorer survival (Bachelot et al, 2003). However, previous studies did not concluded in same results regarding the idea that obese women's tumor has more aggressive phenotype; obesity did not show association with triple negative breast cancer (Maiti et al, 2010), in contrary it was correlated with larger tumor size (Ove Maehle et al, 2001) and more lymphovascular invasion (Gillespie et al, 2010).…”
Section: Discussionmentioning
confidence: 96%
“…The issue is one with important therapeutic implications. Gillespie et al (2010) found that diabetes was associated with an increased risk for 'triple-negative' breast cancer, a tumor type that is negative for ER, PR, and HER2, possesses an aggressive metastatic phenotype, and has a poor prognosis. While this single report requires verification, the metabolic syndrome, with independent association for the blood glucose, has been associated with triple-negative breast cancer (Maiti et al 2010).…”
Section: Commentarymentioning
confidence: 99%